A silent public health threat: emergence of Mayaro virus and co-infection with Dengue in Peru - Aguilar-Luis, Miguel Angel (2021)
Objective: To describe frequency and clinical characteristics of MAYV infection in Piura, as well as the association of this pathogen with DENV. Results: A total of 86/496 (17.3%) cases of MAYV were detected, of which 54 were MAYV mono-infection and 32 were co-infection with DENV, accounting for 10.9% and 6.4%, respectively. When evaluating monoinfection by MAYV the main groups were 18–39 and 40–59 years old, with 25.9% and 20.4% respectively. Co-infections were more common in the age group 18–39 and those > 60 years old, with 34.4% and 21.9%, respectively. The most frequent clinical presentation were headaches (94.4%, 51/54) followed by arthralgias (77.8%, 42/54). During the 8-month study period the most cases were identified in the months of May (29.1%) and June (50.0%).